2020
DOI: 10.1073/pnas.1916715117
|View full text |Cite
|
Sign up to set email alerts
|

LINGO1 is a regulatory subunit of large conductance, Ca 2+ -activated potassium channels

Abstract: LINGO1 is a transmembrane protein that is up-regulated in the cerebellum of patients with Parkinson’s disease (PD) and Essential Tremor (ET). Patients with additional copies of the LINGO1 gene also present with tremor. Pharmacological or genetic ablation of large conductance Ca2+-activated K+ (BK) channels also result in tremor and motor disorders. We hypothesized that LINGO1 is a regulatory BK channel subunit. We show that 1) LINGO1 coimmunoprecipitated with BK channels in human brain, 2) coexpression of LING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…These three genes received a non-zero coefficient for the markedly affected group, and two of them ( HS3ST2 , ROBO1) also received a non-zero coefficient for the unaffected group in ENET analysis ( S3 Table ), suggesting these two genes are markers of interest for assessing disease severity. Additionally, the gene encoding leucine rich repeat and Immunoglobin-like domain-containing protein 1 ( LINGO1) which is involved in the modulation of a voltage-gated potassium channel [ 48 ], and inhibition of axon regeneration [ 49 ] was downregulated in the p . major muscle of Wooden Breast-affected chickens [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…These three genes received a non-zero coefficient for the markedly affected group, and two of them ( HS3ST2 , ROBO1) also received a non-zero coefficient for the unaffected group in ENET analysis ( S3 Table ), suggesting these two genes are markers of interest for assessing disease severity. Additionally, the gene encoding leucine rich repeat and Immunoglobin-like domain-containing protein 1 ( LINGO1) which is involved in the modulation of a voltage-gated potassium channel [ 48 ], and inhibition of axon regeneration [ 49 ] was downregulated in the p . major muscle of Wooden Breast-affected chickens [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are four subtypes of β subunits (β1-β4) (Bhattarai et al, 2014), and mainly β1 subunit is in vascular smooth muscle cells. In addition to β subunits, recent studies have found that the auxiliary subunits of the BK channel also include the γ subunit and subunit LINGO1, which are rich in leucine repeat sequences (Zhang and Yan, 2014;Dudem et al, 2020). Auxiliary subunits are FIGURE 1 | A schematic figure of the ubiquitin proteasome system.…”
Section: Bk Channel Dysfunction In Diabetic Coronary Arterymentioning
confidence: 99%
“…BK channel surface expression is attenuated in channels that are deacylated at the S0–S1 loop, as a result of increased retention in the trans-Golgi network ( 15 ). To assay BK channel surface expression, we exploited an on-cell Western approach to assay surface expression of epitope-tagged BK channels in cell population assays ( 16 , 21 ). In these assays, the FLAG epitope at the extracellular N terminus of the BK channel is used to assay channels that are resident at the cell surface in intact cells, whereas the HA epitope at the intracellular C terminus of the channel allows assay of total BK channel expression in the same cells following cell permeabilization.…”
Section: Resultsmentioning
confidence: 99%